The Regulation and Functions of Endogenous Retrovirus in Embryo Development and Stem Cell Differentiation - Yangquan Xiang; Hongqing Liang (Stem Cells International)
Endogenous retroviruses (ERVs) are repetitive sequences in the genome, belonging to the retrotransposon family. During the course of life, ERVs are associated with multiple aspects of chromatin and transcriptional regulation in development and pathological conditions. In mammalian embryos, ERVs are extensively activated in early embryo development, but with a highly restricted spatial-temporal pattern; and they are drastically silenced during differentiation with exceptions in extraembryonic tissue and germlines. The dynamic activation pattern of ERVs raises questions about how ERVs are regulated in the life cycle and whether they are functionally important to cell fate decision during early embryo and somatic cell development. Therefore, in this review, we focus on the pieces of evidence demonstrating regulations and functions of ERVs during stem cell differentiation, which suggests that ERV activation is not a passive result of cell fate transition but the active epigenetic and transcriptional regulation during mammalian development and stem cell differentiation.